Concentration Determination Disciplines Of Final Projects Using Simple Additive Weighting - Khoirudin Khoirudin; Muhammad Zakki Abdillah; Saifur Rohman Cholil (Jurnal Transformatika, 2018)
A final project is the last project that must be made by a student before obtaining a degree. In practice students often experience confusion in determining the topic to be taken or what the concentration will serve as the topic of the final projects, where the topic is in accordance with their competence.Simple Additive Weighting (SAW) which is also known as weighted linear combination or scoring method is a simple and most often used multi attribute decision technique. This SAW method we trying to use to determine the final projects what is in accordance with the competence of students in the department of informatics Semarang Private University Semarang.The Result of this research can be provide input for students in determining their final projects, taking into consideration the values they acquired during the course. With the results of this research is expected the students will be able to work on their project papers to the maximum.